2022
DOI: 10.1021/acsami.2c05184
|View full text |Cite
|
Sign up to set email alerts
|

A Facile Composite Strategy to Prepare a Biodegradable Polymer Based Radiopaque Raw Material for “Visualizable” Biomedical Implants

Abstract: Enabling a biodegradable polymer radiopaque under X-ray is much desired for many medical devices. Physical blending of a present biodegradable polymer and a commercialized medical contrast agent is convenient yet lacks comprehensive fundamental research. Herein, we prepared a biodegradable polymer-based radiopaque raw material by blending poly(L-lactic acid) (PLLA or simply PLA) and iohexol (IHX), where PLA constituted the continuous phase and IHX particles served as the dispersed phase. The strong X-ray adsor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 70 publications
0
34
0
Order By: Relevance
“…We employed the mold casting method to fabricate the patterned surfaces, as schematically presented in Figure S2, and the topography was controlled with varied array parameters, in particular, heights and diameters. Here, we choose PLLA as the raw material because PLLA as well as its copolymer such as poly­(lactide- co -glycolide) (PLGA) is a kind of polymeric biomaterials widely used in biodegradable implants, and we choose human umbilical vein endothelial cells (HUVECs) as the model cell type because this is an important cell type widely used in biomaterial studies, in particular for cardiovascular systems. Roughness, plateau coverage, stereo coverage, and overall stiffness were calculated and correlated to adhesion behaviors of cells on different micropatterns. It is verified that these important parameters can semi-quantify the effects of surface topography on cell adhesion.…”
Section: Introductionmentioning
confidence: 99%
“…We employed the mold casting method to fabricate the patterned surfaces, as schematically presented in Figure S2, and the topography was controlled with varied array parameters, in particular, heights and diameters. Here, we choose PLLA as the raw material because PLLA as well as its copolymer such as poly­(lactide- co -glycolide) (PLGA) is a kind of polymeric biomaterials widely used in biodegradable implants, and we choose human umbilical vein endothelial cells (HUVECs) as the model cell type because this is an important cell type widely used in biomaterial studies, in particular for cardiovascular systems. Roughness, plateau coverage, stereo coverage, and overall stiffness were calculated and correlated to adhesion behaviors of cells on different micropatterns. It is verified that these important parameters can semi-quantify the effects of surface topography on cell adhesion.…”
Section: Introductionmentioning
confidence: 99%
“…Their drug existed in the form of ropivacaine base nanoparticles prior to being encapsulated in the biomacromolecular hydrogel. Among various biomaterials, the PLGA–PEG-PLGA hydrogel distinguishes itself as an intelligent synthetic biomaterial that can respond to the change of temperature and exhibits a sol–gel transition with spontaneous physical gelation upon heating. Ding and Chen et al even loaded an anesthetic drug into a pertinent polymeric aqueous solution with BUP, which was injected near the nerve to achieve local analgesia .…”
Section: Discussionmentioning
confidence: 99%
“…The next-generation biomaterials are regarded as bioactive and biodegradable. [41] Both cell-material interactions [42][43][44][45][46][47][48][49][50][51][52] and biodegradation regulations [53][54][55][56][57][58] have been investigated, and even some in vivo studies in animal models and clinical research have been reported. [59][60][61][62] It also leads to a serious question about the biosafety along the biodegradation.…”
Section: Discussionmentioning
confidence: 99%